PENGARUH EQUITY DAN ASSET TERHADAP FINANCIAL PERFORMANCE PADA PERUSAHAAN SEKTOR INDUSTRI KONSUMSI - Hartono, Mikhael Jireh; Susanti, Merry (Jurnal Paradigma Akuntansi, 2023)
This research aims at how the effect of Capital Structure, Total Asset Turn Over, Liquidity, Cash Conversion Circle and Firm Size on Financial Performance in consumption industry companies listed on the Indonesia Stock Exchange during 2017-2019. The sample was selected by purposive sampling method and the valid data were 32 companies. The data processing technique uses descriptive-inferential analysis of panel data assisted by the EViews (Econometric Views) 9 Series program and Microsoft Excel 2019. The results of this study indicate that the Debt to Equity Ratio (DER) and Current Ratio (CR) have a significant negative effect on Financial Performance, while the variables Total Asset Turn Over (TATO), Cash Conversion Cycle (CCC), Firm Size (SIZE) have no effect on Financial Performance. The implication of this research is the need for improvement in managing assets and capital to maintain the viability of the company and maximize financial performance and attract investors to the company.